Minimization of Operational Costs for Non-Capitation Claims Verification at BPJS Kesehatan Using a Business Process Reengineering Approach - Raditya Prabaswara; Novandra Rhezza Pratama (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Abstract This study aims to reduce operational costs in the FKTP claim verification business process by using a business process reengineering and TDABC approach and determine the resulting savings. In this study, the data collection method was carried out through participatory observation. The data analysis method in this study uses the Time-Driven Activity-Based Costing (TDABC) approach and business process simulation with iGrafx. The results of this study show that the implementation of Business Process Reengineering (BPR) in the verification process of non-capitation claims significantly improves cost efficiency and operational time. BPR was able to reduce operational costs by 33.1% and cut verification time by 32.9%, through process simplification, elimination of non-value-added activities, and the use of technology such as Optical Character Recognition (OCR). In addition to efficiency, BPR also improves overall organizational accountability and performance, enabling more appropriate resource allocation, reducing the potential for human error, and creating a more transparent, responsive, and sustainable work system. These findings show that BPR is not only a technical tool, but also an organizational transformation strategy that strengthens governance and service quality in the health insurance system.